Surgical Crown Lengthening: Restoring Aesthetics and Function - Bhusal, Sita; Humagain, Manoj; Lamichhane, Simant; Rijal, Arjun Hari (Journal of Nepalese Society of Periodontology and Oral Implantology, 2022)
Short clinical crown affects appearance and retention of the restoration placed within aesthetic zone. Thereafter, Surgical crown lengthening procedure is done to increase crown length for restorative or aesthetic reasons without breaching the biologic width. Herewith, we present a case of crown lengthening procedure along with osseous reduction on maxillary anteriors in a 25 years female patient referred to our department which resulted harmonious appearance and symmetry of tissues on follow up. Aesthetic crown lengthening procedure can be challenging. So, appropriate case selection with accurate diagnostic and interdisciplinary approach are essential for getting enhanced and conservative results in aesthetic areas.